PENGUATAN PENEGAKAN HUKUM KEIMIGRASIAN TERHADAP OVERSTAY DI INDONESIA: PENDEKATAN TEKNOLOGI DIGITAL DAN KEBIJAKAN BEBAS VISA - Komang Sandiasa Dicky Permana; Muhammad Rizky Fathan (Jurnal Riset Multidisiplin Edukasi, 2025)
Global mobility in the digital era has significantly transformed the landscape of immigration governance, reshaping both opportunities and challenges for national border control. Indonesia, as one of Southeast Asia’s major tourist and business hubs, has implemented a visa-free policy to stimulate economic growth, attract foreign visitors, and strengthen cultural exchanges. However, such policies have also created legal vulnerabilities, particularly the administrative violation of overstaying by foreign nationals. The persistent occurrence of overstay, as emphasized by Warren (2017), remains a global issue that demands strategic, technology-driven solutions. This research employs a normative legal approach (Marzuki, 2015) complemented by qualitative descriptive analysis (Moleong, 2011), focusing on the enforcement of Law No. 6 of 2011 concerning Immigration. Data are drawn from primary legal sources, secondary literature, and relevant statistical reports, including those from the Central Statistics Agency (BPS, 2024) and the United Nations World Tourism Organization (UNWTO, 2025). The findings highlight that advancements in artificial intelligence (AI)-based early warning systems, biometric verification, and integrated cross-border databases have enhanced the monitoring and detection of potential violations. Moreover, inter-agency cooperation and the implementation of the selective policy principle (Syahrin, 2018) have proven effective in balancing security concerns with economic interests. This study concludes that continuous innovation, coupled with strong legal enforcement and international collaboration, is essential for addressing the evolving patterns of human mobility in the digital age. The implications extend beyond Indonesia, offering valuable insights for other nations facing similar immigration law enforcement challenges.